The Impact of Revascularisation on Quality of Life in Chronic Mesenteric Ischemia - J. T. M. Blauw; H. A. M. Pastoors; M. Brusse-Keizer; R. J. Beuk; J. J. Kolkman; R. H. Geelkerken; for the Dutch Mesenteric Ischemia Study Group (Canadian Journal of Gastroenterology and Hepatology)
Background. Chronic mesenteric ischemia (CMI) is characterized by long-standing abdominal symptoms due to insufficient mesenteric circulation. Data on the effect of revascularisation on quality of life (QoL) for CMI are scarce. This study is the first to evaluate the impact of revascularisation on quality of life. Methods. Seventy-nine patients with CMI or acute-on-chronic mesenteric ischemia (AoCMI) underwent an intervention of one or more mesenteric arteries between January 2010 and July 2012. QoL before and after intervention was measured with the EuroQol-5D. Preintervention questionnaires were of standard care. Postintervention data were obtained by resending a questionnaire to the patients between February and May 2013. To investigate the clinical relevance of our findings, the minimal clinically important difference (MCID) was used. Since there is no established MCID for CMI, we used the literature reference MCID of inflammatory bowel syndrome (IBS) of 0.074. Results. Fifty-five (69.6%) of 79 patients returned their questionnaire and 23 (29.1%) were completely filled out. There was a significant increase of the median EQ-index score from 0.70 to 0.81 (p=0.02) and a significant reduction of symptoms in the domains usual activities (34.4%) and pain/discomfort (32.3%). There was a significant improvement of 17% in overall current health condition (VAS) (p=0.001). The MCID between baseline and postoperative EQ-5D index score was 0.162, indicating a clinically relevant improvement of quality of life after revascularisation. Conclusion. Quality of life of CMI patients is improved after mesenteric artery revascularisation.